Water erosion aspects of land degradation neutrality to landscape planning tools at national scale - Pena, Selma B. (2020)
The soil erosion by water is a land degradation process identified the Land Degradation Neutrality (LDN) conceptual framework and a soil threat recognized in the Soil Thematic Strategy. It is also a very significant problem in the Mediterranean area. The common cause of land degradation is incorrect land use and management practices, which enhance the importance of planning the future of the landscape. When solving a soil erosion problem, not only land degradation is being reversed, but soil safety is provided: water conservation, biodiversity improvement, ecosystem services provision and better landscape equilibrium. The Land Degradation Neutrality (LDN) target, referred in the United Nations Sustainable Development Goals for 2030, is defined as a state whereby the amount and quality of land resources necessary to support ecosystem functions and services and enhance food security remain stable or increase within specified temporal and spatial scales and ecosystems. Despite some initiatives and recent projects about the achievement of LDN target, the link to landscape planning tools is still lacking. The approach followed in this study incorporates the centric and holistic perspective of soil, and aims to contribute to a definition of a mapping methodology of the areas that should be submitted to land degradation neutrality plans providing ecosystem restoration planning and the co-benefits of restoring soil functions. This goal will be supported by the assessment of the soil conservation status at a national scale (Portugal), using an integrated approach between soil maintenance/improvement and soil degradation, with the current soil cover protection. The evaluation of soil cover protection was established with the interpretation of land use classes and its cover-management factor (C-factor) from the Universal Soil Loss Equation and was tested in three different scenarios: (S1) the higher C-values collected in the research studies (S2) the more recent C-value collected in the research studies and (S3) an adapted scenario with assumptions considered by the authors. The study applied to mainland Portugal showed that Scenario S3 was more equilibrated regarding the distribution of the results (conservation vs. restoration) but was dependent of a set of defined assumptions especially regarding the different forest trees characteristics and management practices performed in Portugal. In this scenario, it was identified that 45.6% of Portugal needs LDN planning towards ecosystem restoration. The proposed methodology also identifies different priority classes of intervention, where the public or private investments could be targeted. Those LDN planning areas are easily framed in the responses to achieve LDN: avoid, reduce or reverse